2010
DOI: 10.1164/rccm.200905-0717oc
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-1 Dampens Pulmonary Inflammation during Acute Lung Injury

Abstract: Pulmonary netrin-1 levels are repressed during ALI. This results in pronounced pulmonary damage, an increased infiltration of neutrophils, and increased pulmonary inflammation. Exogenous netrin-1 significantly dampens the extent of ALI through the adenosine 2B receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
152
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 125 publications
(165 citation statements)
references
References 51 publications
(70 reference statements)
10
152
1
2
Order By: Relevance
“…Ly et al (26) demonstrated that the anti-inflammatory function of netrin-1 was dependent on a member of the UNC family, the UNC5b receptor in vitro through chemotactic migration studies, but they did not translate this finding into in vivo evidence. In recent studies, we demonstrated that netrin-1 dampens hypoxic inflammation through A2BAR and corroborated this during acute lung injury (12,13). In the present study, we investigated the role of netrin-1 during acute exudative inflammation and assessed its role during inflammatory peritonitis.…”
Section: A2barsupporting
confidence: 61%
See 3 more Smart Citations
“…Ly et al (26) demonstrated that the anti-inflammatory function of netrin-1 was dependent on a member of the UNC family, the UNC5b receptor in vitro through chemotactic migration studies, but they did not translate this finding into in vivo evidence. In recent studies, we demonstrated that netrin-1 dampens hypoxic inflammation through A2BAR and corroborated this during acute lung injury (12,13). In the present study, we investigated the role of netrin-1 during acute exudative inflammation and assessed its role during inflammatory peritonitis.…”
Section: A2barsupporting
confidence: 61%
“…This protein gradient possesses bifunctional potential, in that it attracts some axons to, as well as repels other axons from, the ventral midline. Subsequent studies demonstrated the expression of netrin-1 outside the nervous system within the vasculature, a reduction in netrin-1 expression during an acute inflammatory process, and that netrin-1 is a potent inhibitor of myeloid cell migration toward chemotactic stimuli in vitro (12,26). This anti-inflammatory potential of netrin-1 was corroborated by Wang et al (27) during renal ischemia-reperfusion injury.…”
Section: A2barmentioning
confidence: 86%
See 2 more Smart Citations
“…Neutrophils predominate in the lungs of patients with ALI (44) and in many animal models of ALI (45,46). A major constituent of neutrophils is the enzyme MPO (47), which is commonly used to quantify neutrophil accumulation.…”
Section: Concurrent Elevations In Lung Sp and Cox-2 Levels After Burnmentioning
confidence: 99%